Patterns of Endemism in Turkey, the Meeting Point of Three Global Biodiversity Hotspots, Based on Three Diverse Families of Vascular Plants - Noroozi, Jalil; Zare, Golshan; Sherafati, Mahbubeh; Mahmoodi, Mohammad; Moser, Dietmar; Asgarpour, Zahra; Schneeweiss, Gerald M. (Frontiers in Ecology and Evolution, 2019)
Centres of endemism and areas of endemism are important biogeographic concepts with high relevance for conservation and evolutionary biology. Turkey is located at the intersection of three global biodiversity hotspots (Mediterranean, Caucasus, Irano-Anatolian) and harbors remarkable levels of plant diversity and endemism. Nevertheless, hotspots of vascular plant endemics have never been identified using formal quantitative approaches in this diverse region. Here, using data on 1102 endemic taxa of three species-rich families (Asteraceae, Lamiaceae, Boraginaceae) we identified (i) centres of endemism based on three well established indices (endemic richness, range-restricted endemic richness and weighted endemic richness) and (ii) areas of endemism using Endemicity Analysis. A total of 14 grid cells belonging to centres of endemism are identified as hotspots by at least one of the indices. Areas of endemism were identified in south-western Turkey (West-Taurus), southern and central Anatolia (Anatolian Diagonal), in north-eastern Turkey (Pontic-Ala), and in south-eastern Turkey (Hakkari). All hotspots of plant endemism in Turkey included high mountains, which are severely threatened by anthropogenic activities. Although the identified centres of endemism cover only 16% of surface area of Turkey they harbour 59% of the endemic taxa, emphasizing their conservation priority. As the majority of the endemic taxa of Turkey are local endemics and narrowly distributed, protection of the identified hotspots would allow a high proportion of likely threatened species to be protected.